(NiZOTOPNYE METODY W BIOHIMII (B:s (NpEREWOD S ANGLIJSKOGO (B/s - (NaRONOW(B, (Ns(B.s; (NbAEW(B, (Na(B. (Na(B.s; (NbARHA[(B, (Na(B. (Np(B.s; (NgABELOWA(B, (Nn(B. (Na(B.s ((NmOSKWA (B:s (NiNOSTRANNOJ LITERATURY(B,s, 1959)
(NpRILOVENIQ(B: (NS(B. 375 - 387s
Keywords: (NbIOHIMIQs; (NiZOTOPYs